Mycobacterium tuberculosis PE31 (Rv3477) Attenuates Host Cell Apoptosis and Promotes Recombinant M. smegmatis Intracellular Survival via Up-regulating GTPase Guanylate Binding Protein-1 - Ali, Md Kaisar; Zhen, Gong; Nzungize, Lambert; Stojkoska, Andrea; Duan, Xiangke; Li, Chunyan; Duan, Wei; Xu, Junqi; Xie, Jianping (Frontiers in Cellular and Infection Microbiology, 2020)
The Mycobacterium (M.) tuberculosis comprising proline–glutamic acid (PE) subfamily proteins associate with virulence, pathogenesis, and host-immune modulations. While the functions of most of this family members are not yet explored. Here, we explore the functions of ‘PE only’ subfamily member PE31 (Rv3477) in virulence and host-pathogen interactions. We have expressed the M. tuberculosis PE31 in non-pathogenic M. smegmatis strain (Ms_PE31) and demonstrated that PE31 significantly altered the cell facet features including colony morphology and biofilm formation. PE31 expressing M. smegmatis showed more resistant to the low pH, diamide, H2O2 and surface stress. Moreover, Ms_PE31 showed higher intracellular survival in macrophage THP-1 cells. Ms_PE31 significantly down-regulated the production of IL-12p40 and IL-6, while up-regulates the production of IL-10 in macrophages. Ms_PE31 also induced the expression of guanylate-binding protein-1 (GBP-1) in macrophages. Further analysis demonstrates that Ms_PE31 inhibits the caspase-3 activation and reduces the macrophages apoptosis. Besides, the NF-κB signaling pathway involves the interplay between Ms_PE31 and macrophages. Collectively, our finding identified that PE31 act as a functionally relevant virulence factor of M. tuberculosis.